1981
DOI: 10.1113/jphysiol.1981.sp013589
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and diminution of mechanical tension evoked by staircase and by tetanus in rat muscle

Abstract: SUMMARY1. Potentiation of the isometric twitch tension was compared during and after the staircase and after tetanic stimuli in the fast-twitch extensor digitorum longus muscle of adult Lewis rats at 37-380C.2. With up to 250 stimuli the potentiation rose with an increase in both the frequency and number of stimuli in the staircase (2-5/sec) and the tetanus (100-167/sec). After a tetanus of 375 stimuli (125/sec) the potentiation was smaller.The potentiation 2 sec after a tetanus of250 stimuli (167/sec) was + 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 27 publications
7
74
1
1
Order By: Relevance
“…It is known that the staircase response is obtained by an increased intensity of activation, not a prolongation of activation (14,20). In the control and sham animals prior to dantrolene treatment, R-LC phosphorylation probably plays an important role in the staircase response.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the staircase response is obtained by an increased intensity of activation, not a prolongation of activation (14,20). In the control and sham animals prior to dantrolene treatment, R-LC phosphorylation probably plays an important role in the staircase response.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent hindlimb muscles, for example, an increased isometric twitch force is often observed during low frequency contractile activity or following brief, high frequency contractile activity (i.e. staircase and post-tetanic potentiation, respectively) (Close and Hoh, 1968a;Krarup, 1981a). Biochemical studies illustrate that the same cytosolic Ca 2+ signal that activates muscle contraction also generates a signalling cascade that phosphorylates the RLC in a stimulation frequency-and durationdependent manner (Klug et al, 1982;Manning and Stull, 1982;Moore and Stull, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The gradient between skin and muscle temperature is difficult to predict. Heir et al 9 found that skin temperature averaged 2.2 ~ C below muscle temperature, which in turn was 0.8~ below core temperature. However, it appears that in that investigation the hand under study was exposed to ambient operating room temperatures.…”
Section: Changes In Hand Temperature With Induction Of Anaesthesiamentioning
confidence: 99%